Where should reading strategies be taught first: In Persian (L1), English (L2) or Arabic (L3)? / Seyed Hassan Talebi - Talebi, Seyed Hassan (Universiti Teknologi MARA, Kedah, 2015)
This paper touches upon issues and trends in language transfer studies and reading research. Then, a brief report of three separate published papers by the author on the transfer of reading strategies from L1 to L2, L2 to L3 and L2 to L1 will be provided. In language transfer studies the idea is that languages affect each other. But, from where is it logical to lay the stepping stones of strategic reading if it is believed awareness of reading strategies transfer from one language to another in a multilingual mind? It seems it is logical and cost effective to improve strategic reading competence in L1 if it is shown that learners' skills and experiences in language learning are cross-linguistically linked together.